Lifestyle-related risk factors and their cumulative associations with hippocampal and total grey matter volume across the adult lifespan: a pooled analysis in the European Lifebrain consortium - Binnewies, J; Nawijn, L; Brandmaier, AM; Baaré, WFC; Boraxbekk, C-J; Demnitz, N; Drevon, CA; Fjell, AM; Lindenberger, U; Madsen, KS; Nyberg, L; Topiwala, A; et al. (Elsevier, 2023)
Background: Lifestyle-related risk factors, such as obesity, physical inactivity, short sleep, smoking and alcohol use, have been associated with low hippocampal and total grey matter volumes (GMV). However, these risk factors have mostly been assessed as separate factors, leaving it unknown if variance explained by these factors is overlapping or additive. We investigated associations of five lifestyle-related factors separately and cumulatively with hippocampal and total GMV, pooled across eight European cohorts. Methods: We included 3838 participants aged 18-90 years from eight cohorts of the European Lifebrain consortium. Using individual person data, we performed cross-sectional meta-analyses on associations of presence of lifestyle-related risk factors separately (overweight/obesity, physical inactivity, short sleep, smoking, high alcohol use) as well as a cumulative unhealthy lifestyle score (counting the number of present lifestyle-related risk factors) with FreeSurfer-derived hippocampal volume and total GMV. Lifestyle-related risk factors were defined according to public health guidelines. Results: High alcohol use was associated with lower hippocampal volume (r=-0.10, p=0.021), and overweight/obesity with lower total GMV (r=-0.09, p=0.001). Other lifestyle-related risk factors were not significantly associated with hippocampal volume or GMV. The cumulative unhealthy lifestyle score was negatively associated with total GMV (r=-0.08, p=0.001), but not hippocampal volume (r=-0.01, p=0.625). Conclusions: This large pooled study confirmed the negative association of some lifestyle- related risk factors with hippocampal volume and GMV, although with small effect sizes. Lifestyle factors should not be seen in isolation as there is evidence that having multiple unhealthy lifestyle factors is associated with a linear reduction in overall brain volume.